Analisis Cemaran Bakteri Coliform Pada Minuman Jajanan Dengan Metode MPN (Most Probable Number) - Ervina Surnianingsi Jufri; Ismail Rahman (Journal Syifa Sciences and Clinical Research, 2022)
Coliform bacteria contamination of food and beverages may result from various causes, one of which is faecal contamination, leading to serious health issues. Drinking water contamination of coliform bacteria 50/100 mL has been found to be responsible for diarrhea episode. Local regulation has determined the cut-off point of its contamination within commercial beverages not to exceed 3/mL. No such study has ever been conducted in Ternate. To determine the exact value of coliform bacteria within street beverages sold in various city parks in Ternate. This descriptive was carried out through laboratory testing of street beverages obtained from various city parks in Ternate. The most probable number test for coliform bacteria was carried out at the Technical Implementation Unit, Basic and Integrated Laboratory, North Maluku from December 2021-January 2022. The presumption test and the affirmation test were conducted accordingly. From 22 instant powdered ice drinks samples obtained from Toboko, Falajawa 1, Nukila, Landmark, and Film Benteng parks, 90,9% contained coliform bacteria exceeding the cut-off value. Coliform bacteria contamination in the city parks within Ternate has exceeded the quality standard threshold based on Indonesian National Standard 7388 of 2009. Further research is needed to confirm this.